Ke in utterances: uses and functions of the Xhosa discourse marker ke - Masinyana, Abdul-Malik Sibabalwe Oscar (African Studies, 2014)
Discourse Markers (DM) have been identified in so many languages, utterance contexts, and studied from so many angles and theoretical approaches (Ogoanah, 2011;; Jantjies, 2009;; Jabeen, et. al, 2011;; Dér and Markó, 2010;; Verdonik et.al, 2007;; Li, 2010;; Hernández, 2011;; Camiciottoli, 2009), so much that another study hardly seems necessary. Focusing on Xhosa, a linguistic context where hardly any work is being done on DMs, this thesis argues that the Xhosa particle ke is a DM that is popular in, but not restricted to, oral utterances and a DM that is present even in 19th century Xhosa utterances. At present, the general agreement between Xhosa grammars and dictionaries is that ke is either/and/or a conjunction or conjunctive, an interjective, an adverb, an enclitic, an expletive or a form word with a variety of translation equivalents in English. Using a DM analysis framework provided by Schourup (1999) ? which corresponds closely with the pioneering framework by Schiffrin (1987) and also contains elements of Fraser's model (1996, 2009) ? this thesis examines these three claims and concludes that ke is mainly a DM (over and above being one or more or all of the present classifications) and should be presented as such in future Xhosa dictionaries, grammars and linguistic research.